Natural Fibre Textile Nano-Level Surface Modification (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
A variety of applications requires production of textile materials with specially designed surface properties. Surface coating by metallic materials have attracted a lot of attention due to their special surface properties, such as UV-absorbsion, antimicrobial, anti-fungicidal and ect. The paper describes the process of vacuum evaporation and magnetron sputtering of copper layers on cotton textile materials and analysis of the metal coated textile surface morphology by laser laboratory complex. The textile samples have been finished by magnetron sputtering and vacuum evaporation technologies and tested for bonding strength, light reflection and light passing properties. The paper presents and discusses the results of the experiment.